A 2‐Year Randomized Controlled Trial With Low‐Dose B‐Vitamin Supplementation Shows Benefits on Bone Mineral Density in Adults With Lower B12 Status. (14th October 2022) - Clements, Michelle; Heffernan, Maria; Ward, Mary; Hoey, Leane; Doherty, Leanne C; Hack Mendes, Roberta; Clarke, Michelle M; Hughes, Catherine F; Love, Ingrid; Murphy, Shauna; McDermott, Eilish; Grehan, Jennifer; et al.
ABSTRACT: Folate, vitamins B12, B6, and riboflavin are required for one‐carbon metabolism and may affect bone health, but no previous randomized trial has investigated all four nutrients in this context. We investigated the effect of low‐dose B‐vitamins for 2 years on bone mineral density (BMD) in a dual‐centered, 2‐year randomized controlled trial (RCT) in adults aged ≥50 years. Eligible participants not consuming B‐vitamin supplements or fortified foods >4 times weekly were randomized to receive daily either combined folic acid (200 μg), vitamin B12 (10 μg), vitamin B6 (10 mg), and riboflavin (5 mg), or "active" placebo, whereby both the intervention and placebo groups received vitamin D (10 μg). BMD was assessed before and after intervention using dual‐energy X‐ray absorptiometry (DXA) scanning of the total hip, femoral neck, and lumbar spine (L1 to L4). Of 205 eligible participants randomized, 167 completed the trial in full. B‐vitamin intervention resulted in increases in serum folate ( p < 0.001), serum B12 ( p < 0.001), and plasma pyridoxal‐5‐phosphate ( p < 0.001) and decreases in functional biomarkers of B‐vitamin status, erythrocyte glutathione reductase activation coefficient ( p < 0.001), serum methylmalonic acid (MMA; p < 0.001), and serum total homocysteine ( p < 0.001). B‐vitamin intervention had no overall effect on BMD, which declined in both treatment groups by approximately 1% (ranging from −0.7% to −1.4%). However, in participants with lower baseline B12 status (serum B12 <246 pmol/L or MMA ≥0.22 μmol/L), B‐vitamin intervention reduced the 2‐year BMD decline versus placebo: adjusted mean (95% confidence interval [CI]) change of −0.003 (−0.008, 0.002) versus −0.015 (−0.021, −0.010) g/cm 2 at the total hip and −0.004 (−0.010, 0.001) versus −0.013 (−0.018, −0.007) g/cm 2 at the femoral neck. In conclusion, the findings indicate that although low‐dose B‐vitamin intervention for 2 years had no overall effect on BMD, improving B‐vitamin status appears to have specific benefits for bone health in adults with lower B12 status. © 2022 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).